Accuracy of EOS Imaging Technology in Comparison to Computed Tomography in the Assessment of Vertebral Rotational Orientation in Instrumented Spines in Adolescent Idiopathic Scoliosis. Issue 2 (15th January 2021) - Jiang, Fan; Simões, Leonardo; Ouellet, Jean; Saran, Neil
Abstract : Study Design: Retrospective radiographic reliability study. Objective: The aim of this study was to assess the validity of EOS 3D imaging technology in the determination of vertebral rotations in the spine of patients with previous instrumentation. Summary of Background Data: There is a lack of evidence on the accuracy of vertebral rotational measurement using EOS 3D morphological analysis in the instrumented spine. Methods: A retrospective review of 31 patients with adolescent idiopathic scoliosis (AIS) who underwent instrumented fusion and postoperative computed tomography (CT) scans of the spine was performed. Vertebral rotations of the apex vertebra, the uppermost (UIV) and lowermost (LIV) instrumented vertebra, the noninstrumented vertebra one level cranial to the UIV (UIV + 1) and one level caudal to LIV (LIV + 1) were determined using EOS 3D reconstruction. The vertebral rotation was also measured using reformatted CT axial images. Relative vertebral rotational difference (VRD) were calculated for UIV to apex, UIV + 1 to apex, LIV to apex, LIV + 1 to apex, UIV to LIV and UIV + 1 to LIV + 1. Paired t tests were used to compare the VRD measured using the two different imagining modalities. For values where P > 0.05, the Bland-Altman plot was used to assess the agreement between the measures. Interclass correlation (ICC) was used to determine interobserver and intraobserver reliabilities of EOS and CT measurements. Results: EOS analysis of relative VRD was found to be significantly different from that of CT for UIV to apex ( P = 0.006) and UIV + 1 to apex ( P = 0.003). No significant differences were found for LIV to apex ( P = 0.06), LIV + 1 to apex ( P = 0.06), UIV to LIV ( P = 0.59) and UIV + 1 to LIV + 1 ( P = 0.64). However, Bland-Altman plots showed that agreement was poor, and variance was beyond acceptable. ICC showed good interobserver and good to very good intraobserver reliability for EOS. Conclusion: EOS 3D morphological analysis of VRD in the instrumented levels of the spine demonstrated significant difference and unacceptable variance in comparison to CT measurement. Level of Evidence: 4 Abstract : The presence of spinal instrumentation can affect the accuracy of vertebral rotation measurement by EOS 3D morphological analysis. The implant can obscure the proper assessment of bony anatomy, and the upper segment of the spine appears to be more affected than the lower. Interobserver and intraobserver reliability, however, remains good.